Endoscopic ultrasound in the monitoring of the intestinal allograft - Per Hedenström; Mihai Oltean; Riadh Sadik; Jonas Varkey; Gustaf Herlenius (BMJ Open Gastroenterology)
Objective Chronic rejection (CR) of the small intestinal allograft includes mucosal fibrosis, bowel thickening and arteriopathy in the outer wall layers and the mesentery. CR lacks non-invasive markers and reliable diagnostic methods. We evaluated endoscopic ultrasound (EUS) as a novel approach for monitoring of the intestinal allograft with respect to CR.Design In intestinal graft recipients, EUS and enteroscopy with ileal mucosal biopsy were performed via the ileostomy. At EUS, the wall thickness of the intestinal graft was measured in standard mode, whereas the resistive index (RI) of the supplying artery was assessed in pulsed Doppler mode. At enteroscopy, the intestinal mucosa was assessed. Findings were compared with histopathology and clinical follow-up.Results EUS was successfully performed in all 11 patients (adequate clinical course (AC) n=9; CR n=2) after a median interval of 1537 days (range: 170–5204), post-transplantation. The total diameter of the wall (layer I–V) was comparable in all patients. Meanwhile, the diameter of the outermost part (layer IV–V; that is, muscularis propria–serosa) was among the two CR patients (range: 1.3–1.4 mm) in the upper end of measurements as compared with the nine AC patients (range: 0.5–1.4 mm). The RI was >0.9 in both CR patients, while the RI was ≤0.8 in all AC patients. Both CR patients had abnormal findings at enteroscopy and histopathology and deceased during follow-up.Conclusion EUS is a promising tool providing detailed information on the intestinal graft morphology and rheology, which may be used for assessment of potential CR in long-term follow-up of intestinal allograft recipients.